Humanism Learning Theory And Mathematics Learning - Ikhbariaty Kautsar Qadry; Syahrullah Asyari; Nur Ismiyati; Muhammad Nurhusain (Universitas Negeri Makassar, 2021)
Humanism that is widely understood in this modern era is renaissance humanism which is one of the atheist philosophies. Humans are respected. Even humans are made as the center of truth by glorifying reason and rejecting theism or supernaturalism. The earliest thinkers in education based on this notion in the modern age were John Dewey, Johann Pestalozzi, and Maria Montessori. This understanding became ligitimate after The Association of Humanistic Psychology was founded in 1962. At that time, the humanistic movement began to influence psychology, education, and the workplace. This humanistic movement also gave birth to humanistic psychology with a character, Abraham H. Maslow. Maslow’s Theory of Needs, then had a significant effect on education, especially in the development of learning theories, including andragogy, transformational learning, and independent learning. Maslow’s humanistic learning theory encourages innovation and creativity. It is believed in this theory that everyone is responsible for their own learning as well as learning from those around them. This theory encourages students to be in a supportive and safe environment, so they are comfortable asking questions and exploring new concepts and possibilities. This theory states that the best learning occurs when the whole person (cognitive, affective, psychomotor) is involved, taking into account the totality of human experience. This theory has also drawn criticism. Some experts think that this theory is not based on rigorous scientific experience. Meanwhile, other experts review the philosophy that underlies this theory from the context of values, religion, culture and ideology of the Indonesian nation. However, the learning theory built on the philosophy of humanism can also be applied in mathematics education. A good example of this is the differentiation of mathematics learning. Through this learning differentiation, all students learn in different ways and according to their level of difficulty in understanding mathematical concepts. In other words, each student gets treatment according to his or her need